Additive manufacturing of affinity hydrogels for controlled biomacromolecule delivery in early osteoarthritis - Loxley, George (2023)
Osteoarthritis (OA) is a disease that is characterised by the progressive erosion of articular cartilage, synovial inflammation, subchondral bone remodelling, and osteophyte formation. Osteoarthritis is a leading cause of disability and affects over 500 million people world-wide. There is a lack of disease modifying anti-osteoarthritic drugs (DMAODs) which means the disease pathobiology cannot be stopped, resulting in existing treatments having transient efficacy and being focused mainly on symptom management. Pro-inflammatory signalling is a key driver of OA progression at the early stages of the disease and is the result of an imbalance in M1 and M2 macrophage signalling. Regenerative medicine approaches for OA have historically neglected to target inflammation and osteochondral tissue engineering still remains elusive. An early intervention therapy promoting M2 macrophage polarisation may balance immune signalling in the osteoarthritic joint and decelerate progression to retain cartilage tissue that would otherwise be irreversibly lost.